A Plasma Biochemical Analysis of Acute Lead Poisoning in a Rat Model by Chemometrics-Based Fourier Transform Infrared Spectroscopy: An Exploratory Study - Tian, Wenli; Wang, Dan; Fan, Haoran; Yang, Lujuan; Ma, Gang (Frontiers in Chemistry, 2018)
In this work, we explored to use chemometrics-based Fourier transform infrared (FTIR) spectroscopy to investigate the plasma biochemical changes due to acute lead poisoning (ALP) in a rat model. We first collected the FTIR spectra of the plasma samples from the rats with and without suffering from ALP. We then performed the chemometric analysis of these FTIR spectra using principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). We found that the chemometrics-based FTIR spectroscopy can discriminate the rats with and without ALP. Further analysis on the PLS-DA regression coefficient revealed that the spectral changes, in particular, corresponding to the biochemical changes of proteins in the plasma may be used as potential spectral biomarkers for the diagnostics of lead poisoning. Our work demonstrates the potential of chemometrics-based FTIR spectroscopy as a promising tool for the biochemical analysis of plasma that could consequently enable an objective, convenient and non-destructive diagnostics of lead poisoning. To the best of our knowledge, this work is the first application of chemometrics-based FTIR spectroscopy in the diagnostics of lead poisoning.